1996
DOI: 10.1001/archsurg.1996.01430140023007
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic vs Private Transportation of Trauma Patients

Abstract: Patients with severe trauma transported by private means in this setting have better survival than those transported via the EMS system. Large prospective studies are needed to identify the factors responsible for this difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(104 citation statements)
references
References 19 publications
3
92
1
6
Order By: Relevance
“…The removal of IMCW victims for treatment by relatives and friends was prompt in majority of the cases probably accounting for part of the overall low mortality recorded for those who had CT scan as compared to the PMI group. This is in agreement with reports from a previous study which has shown that traumatized patients who are transported by the emergency medical system do experience a higher mortality than their counterparts transported by non emergency medical system means such as friends, relatives, or bystanders 23 . It has been estimated that for every 10minutes of delay in definitive treatment, survival for certain types of injuries decreases by 10%, suggesting that a prolonged injury-to-treatment interval is deleterious especially in severely injured.…”
Section: Discussionsupporting
confidence: 93%
“…The removal of IMCW victims for treatment by relatives and friends was prompt in majority of the cases probably accounting for part of the overall low mortality recorded for those who had CT scan as compared to the PMI group. This is in agreement with reports from a previous study which has shown that traumatized patients who are transported by the emergency medical system do experience a higher mortality than their counterparts transported by non emergency medical system means such as friends, relatives, or bystanders 23 . It has been estimated that for every 10minutes of delay in definitive treatment, survival for certain types of injuries decreases by 10%, suggesting that a prolonged injury-to-treatment interval is deleterious especially in severely injured.…”
Section: Discussionsupporting
confidence: 93%
“…As previously discussed, this may be due to proximity or field triage guidelines used by the trained EMS personnel. For children with minor injuries, EMS transportation may not be necessary; 18,[20][21][22] however, for parents of moderately injured children who forego EMS transportation due to the expensive cost and co-pay, communities may benefit from education about the increased capabilities of pediatric designated trauma centers to care for their children.…”
Section: Discussionmentioning
confidence: 99%
“…A second caveat is that pediatric trauma patients who used EMS were not matched by inhospital mortality risk or underlying factors determining LOS, such as transportation time, an important factor in treating severely injured patients. 8,22 The first hour after injury, or "golden hour," is important in determining trauma outcomes, and although EMS transport ensures appropriate field triage, it may take more than one hour to receive care. Our study was not able to control for transport time because it was not reported by private transporters.…”
Section: Discussionmentioning
confidence: 99%
“…8,[11][12][13] The time interval from injury to control of hemorrhage is the dominant variable defining patient survival. 8,[12][13][14][15] As a result, urban centres with advanced prehospital systems and experienced trauma surgeons (i.e., rapid decision-making) often show impressive survival characteristics despite major vascular injuries.…”
Section: Initial Assessment and Resuscitationmentioning
confidence: 99%